A prospective randomized double-blind study comparing the dose-response curves of epidural ropivacaine for labor analgesia initiation between parturients with and without obesity - Huang, Xiao-Dong; Qiu, Xiao-Xiao; Wang, He-Jie; Jin, Xia-Fang; Xiao, Fei (Frontiers in Pharmacology, 2024)
Background: Previous studies have explored the median effective concentration (EC50) of ropivacaine for labor epidural analgesia in parturients with obesity. However, the clinical relevance of the 90% effective concentration (EC90) remains unclear. This study aimed to determine and compare the dose–response curve of epidural ropivacaine for labor analgesia between parturients with and without obesity. Methods: Parturients were divided into two groups based on body mass index (BMI): group N, consisting of parturients with BMI <30 kg/m2, and group O, consisting of parturients with BMI >30 kg/m2. Within each group, the patients were randomized to receive one of five concentrations (0.0375%, 0.075%, 0.1125%, 0.15%, or 0.1875%) of epidural ropivacaine for labor analgesia. Analgesia was induced with a loading dose of 15 mL of the assigned concentration. Visual analogue scale (VAS) scores were recorded at baseline and 30 min post-dose to calculate the response (%) using the formula [(baseline VAS pain score—VAS pain score at 30 min)/baseline VAS pain score] ×100%. The EC50 and EC90 values were determined via nonlinear regression analysis. Results: The EC50 and EC90 values of ropivacaine were 0.061% (95% confidence interval [CI], 0.056%–0.066%) and 0.177% (95% CI, 0.152%–0.206%) in group N and 0.056% (95% CI, 0.051%–0.061%) and 0.161% (95% CI, 0.138%–0.187%) in group O, respectively. No significant differences were observed in the EC50 and EC90 values between the two groups (p-values = 0.121 and 0.351, respectively. Conclusion: In conclusion, within the parameters of this study, our findings suggest that obesity, characterized by a mean BMI value of 30.9, does not significantly influence the EC50 and EC90 values of epidural ropivacaine for labor analgesia. Further investigations are warranted to elucidate the dose-response relationship between ropivacaine and obesity with higher BMI values. Clinical trial registration:https://www.chictr.org.cn/showproj.html?proj=190747, Identifier ChiCTR2300073273.